Analisis Kritis Pelanggaran Kode Etik Profesi Akuntan Publik Di Indonesia - Amrizal Amrizal (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
Public accountant is a profession that a tremendous respect for moral values and ethics, the public accounting profession in order to earn a respectable place in the public it is necessary to build public trust and public interest. Conflict of interest occurs when the practitioners of public accounting as a profession and a public accounting firm as a service company should provide quality services to its clients. It is a challenge to test idealism, morals and ethics of the accountant. Violation of professional standards of public accountant is a reflection of moral and ethical practitioners of public accountants. Several violations such as: audit deadline, the collusion between the accountant with a client, do not keep integrity and competency. Violating the independence, morally or in fact. The impact of code violations committed public accountant including losses to investors or other stakeholders who utilize public accountant audit results. Disappear or diminished public confidence in the public accounting profession, the accounting profession will ultimately harm themselves. Public accountant office conducting violations against the public accounting profession, the trend is likely to increase, this is caused by the growing public access to public accounting profession itself, as long as the public accountant to be behind the Great Wall of that can not be reached by the public or the media.